La Sûreté du Québec des origines à nos jours : quelques repères historiques - Leclerc, Jean-François (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
The history of the police in Canada is a field that has been little explored. This is all the more so in the case of the police corps of Quebec, the only valid monograph on the subject being one on the Montreal police. This article gives a general outline of the administrative history of the provincial police of Quebec, the “Sûreté du Québec”, since its creation in 1870 by the provincial government. The idea of creating a police force under State control was not new, going back to the first «modern» police established in 1838 in Quebec city and Montreal during a time of rebellion, by an Order in Council of governor Durham. An unsuccessful attempt was made to establish one during the 1850s. It was in 1870 that the «provincial police» were set up in Quebec City, the capital, mainly to have a force to intervene in riots and strikes. Municipalities requiring them could also obtain their services. This police corps was reduced after 1878 to become a mere guard of the Parliament which also served the Department of the Attorney General. After that, great changes were made with the integration of other police and government services : the Bureau of Provincial Detectives of Montreal in 1922, the liquor and highway police in 1934 and 1936, which in 1938 become branches of the Provincial Police. In 1938, the Duplessis government undertook to extend the provincial police by opening up stations throughout the province. After 1960, the Lesage government completed the merging of the various branches, sought to eliminate political influence in the hiring of police and opened the first training school for policemen. The Provincial Police became the Sûreté du Québec in 1968, when an administrative restructuring was started, inspired by the methods used in private enterprise, which gave its form to today's Sûreté.